Analisis Kinerja Portofolio Optimal Pada Saham Perusahaan Transportasi dan Logistik Dengan Metode Sharpe, Treynor, dan Jensen Periode 2020-2024 - Amalia, Rifdah; Safitri, Maria; Prawitasari, Dian; Kusuma, Pradana Jati (Bisnis-Net, 2025)
This study aims to identify the optimal portfolio performance of transportation and logistics company stocks for the period 2020-2024. The single index model is used in the formation of optimal portfolios and stock portfolio performance assessment using the Sharpe, Treynor, and Jensen methods. This research is descriptive research with a quantitative approach. Types and sources of data come from secondary data. The data in this study were analyzed with Microsoft Excel 2021. The purposive sampling technique was used in sampling in this study. Based on the formation of an optimal portfolio using a single index model, 12 stocks were selected as part of the optimal portfolio from a total of 17 sample stocks studied, namely  SMDR, SAPX, TMAS, HELI, LRNA, JAYA, TNCA, TRUK, SAFE, ASSA, AKSI, and  WEHA.  The analysis results show that the best performance measurement is the Treynor Index which has the highest value of other calculations with a total value of 4,296.